Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper discusses Ireland's trade and financial linkages with key partner countries. The paper uses a vector autoregression to examine the impact of shocks to partner country GDP and shocks to Irish competitiveness on Irish GDP. Two main findings are that shocks to U.S. GDP have a much larger impact on the variance of Irish GDP than shocks to the euro area or the United Kingdom. The paper also uses the IMF's Global Fiscal Model to compare the effects of alternative fiscal adjustment strategies on employment and growth.